The four-headed dragon - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1981)
The Hardy boys track a criminal who plans to use an invention designed as a peaceful aid to the secret Four-Headed Dragon organization behind the Iron Curtain to harm the free world instead.